INTERACTIVITY AS PROSOCIAL DRIVER IN THE RTVE LAB - Dra. Saida SANTANA MAHMUT; Dr. Gustavo MONTES RODRÍGUEZ; Dr. Vicente SANZ DE LEÓN (Fonseca, Journal of Communication, 2024)
In recent years, there has been a proliferation of immersive journalism aimed at eliciting empathy from its audience (Milk, 2015), enabling users to experience the facts in the first person, facilitating a feeling of "presence" (De la Peña et al., 2010) and consequently fostering prosocial behaviors (i.e., positive behaviors or interactions), thereby turning the environment into an "empathy machine" (Milk, 2015) or an "emotional geography" (Baía, 2023, p. 137). Just as Archer and Fischer (2018) identified empathy-generating elements of 360-degree video news stories, the objective of this study is to determine whether four interactive products dealing with social issues created by the Spanish national broadcaster’s Laboratory of Audiovisual Innovation and New Narratives (RTVE Lab) in 2023 —Rescate en el Mediterráneo, 8M: cómo el machismo marcó nuestra adolescencia, Cadáveres de Hormigón, and El lado oscuro de los filtros— provide a sufficient level of viewer immersion to promote prosocial behaviors. To this end, the technological, narrative, and thematic aspects of these products are analyzed, as well as the product concept and type of content. The results reveal that the RTVE Lab’s deliberate choice of social content and its use of interactivity and/or transmediality give the products selected for analysis prosocial characteristics, as they are thus able to generate “place illusion” and “plausibility illusion” (Slater 2009) and to elicit viewer empathy. The findings also confirm that audience immersion is possible using interactive formats without 360º video, whose use has been declining since 2018 (Pérez-Seijo, 2021).